PENGELOLAAN SEKTOR PARIWISATA MELALUI PENDEKATAN PARTISIPASI STAKEHOLDERS DI KAWASAN WISATA DESA SAWARNA KABUPATEN LEBAK PROVINSI BANTEN - Suwaib amiruddin; Yana Suharyana; Agus Aan Hermawan (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2022)
The management concept has an orientation for future independence and participation is an approach to involve local resources in managing their environment. This approach is a strategic thing in encouraging tourism management at the village level in Indonesia and especially in Sawarna Beach. The purpose of the study was to examine the sustainable use of local resources from the participation of stakeholders in tourism management in Sawarna Village to support the economic income of local communities. The method used is a qualitative approach. Collecting data through observation, interviews and documentation. The results of the study found that tourism management through a participatory approach involving the community was carried out through participation in institutional management, participation in managing the carrying capacity of facilities, participation in marketing management, and participation in promotional innovations.